Leveraging Convergent Encryption for Secure and Efficient Data Protection in Distributed Cloud Systems - Gajanan Kishanrao Mangnale (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The rapid expansion of distributed cloud systems has led to an unprecedented increase in data generation, storage demands, and security concerns. Efficient data management techniques such as deduplication have become essential for reducing storage overhead and optimizing bandwidth usage. However, traditional encryption techniques hinder deduplication because identical data encrypted with different keys produces distinct ciphertexts. Convergent Encryption (CE), also known as message-locked encryption, addresses this challenge by generating encryption keys directly from the data content, thereby enabling secure deduplication while preserving data confidentiality. This paper investigates the application of convergent encryption in distributed cloud environments, focusing on achieving a balance between storage efficiency and data security. It presents a comprehensive analysis of CE mechanisms, system architecture, and workflow, along with a discussion of existing solutions such as Proof of Ownership and hybrid encryption models. The study further proposes an enhanced framework that integrates secure key management, access control, and probabilistic data structures like Bloom filters to improve performance and mitigate security risks. Despite its advantages, convergent encryption is vulnerable to several security threats, including dictionary attacks, brute-force attempts, and confirmation-of-file attacks. To address these challenges, the paper explores advanced mitigation strategies such as salting techniques, rate limiting, trusted key servers, and multi-cloud storage approaches. Performance evaluation indicates that CE significantly reduces storage redundancy and network overhead while maintaining acceptable levels of security when combined with additional safeguards. The findings suggest that convergent encryption, when augmented with robust security enhancements, can serve as a viable solution for secure and efficient data protection in large-scale distributed cloud systems. The paper concludes by highlighting future research directions, including the integration of artificial intelligence for anomaly detection, blockchain-based key management, and quantum-resistant encryption schemes to further strengthen cloud data security.